A novel assembly of MoS2-PTFE solid lubricants into wear-resistant micro-hole array template and corresponding tribological performance. (August 2019) - Wang, A.H.; Xia, J.; Yang, Z.X.; Xiong, D.H.
Highlights: Micro-hole templates were produced by laser drilling on the laser-clad wear-resistant coatings, mixtures of MoS2 and PTFE powders were uniformly deposited into the laser-drilled micro-hole templates by electrophoretic deposition. Microwave sintering at 300 °C densified the EPD coatings without oxidization of MoS2, but increasing sintering temperature to above 350 °C resulted in oxidization of MoS2 into MoO2 . The friction coefficient of the MoS2 -10wt.%PTFE coating with 20% micro-hole density sintered at 300 °C presented the lowest friction coefficient amongst the all coatings. Abstract: Special blind micro-hole array templates were constructed by fiber laser drilling on laser-clad wear-resistant Fe-based alloy coatings with aim to carry and to preserve solid lubricants into micro-hole reservoir. The influence of laser parameters on the morphology of blind holes was investigated. The blind U-shape micro-hole array templates, which are the most suitable for subsequent electrophoretic deposition (EDP), were fabricated by the optimized laser drilling parameters. Different lubricant mixtures of MoS2 and PTFE powder were assembled into the blind micro-hole array templates with different micro-hole density by EDP. The deposited mixtures of MoS2 and PTFE powder were densified by microwave sintering. The tribological performance evaluated by a ring-on-block wear tester indicated that the 20% micro-hole density template assembled with MoS2 -10wt%PTFE powder presented the lowest friction coefficient.